2012
DOI: 10.1159/000341886
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Sugar-Sweetened Beverages in Relation to the Metabolic Syndrome among Iranian Adults

Abstract: <b><i>Background:</i></b> Few data are available linking intake of sugar-sweetened beverages (SSBs) with the metabolic syndrome. Furthermore, findings from these studies are inconsistent and most are from Western societies; no information is available in this regard from Middle Eastern populations. <b><i>Objective</i></b>: This study was conducted to assess the relationship between SSB consumption and metabolic syndrome in an Iranian adult population. <b>&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 98 publications
(59 reference statements)
6
26
0
Order By: Relevance
“…[11][12][13][14][18][19][20][21][22][23][24][25] The process of study selection is shown in Figure 1 [11][12][13][14][18][19][20][21][22][23][24][25] The process of study selection is shown in Figure 1 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[11][12][13][14][18][19][20][21][22][23][24][25] The process of study selection is shown in Figure 1 [11][12][13][14][18][19][20][21][22][23][24][25] The process of study selection is shown in Figure 1 …”
Section: Resultsmentioning
confidence: 99%
“…18,19,23 Two studies evaluated the risk of metabolic syndrome with sweetened beverage consumption in younger cohorts (children, adolescents or young adults) and were excluded in a sensitivity analysis. Consequently, gender-specific adjusted hazard ratios extracted from these studies allowed analysis of metabolic syndrome associated with soft drink consumption to be stratified by gender.…”
Section: Study Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have assessed the relationship between the consumption of beverages and specific outcomes: for example, the intake of sugar-sweetened beverages (SSBs) and metabolic syndrome (MetS) or type 2 diabetes (T2DM) [3], hypertension [4,5,6] and other cardiometabolic variables [7]; or the intake of drinking water and its relationship to cardiovascular diseases (CVD) [8]. However, the results in some cases are controversial [9,10,11] and it is probably partially attributable to the difficulties in assessing the real fluid pattern [12]. Water is an essential nutrient for life [13] and the research on its contribution to human health is very important, so it is essential that the technique used to assess the consumption of different types of beverage is sufficiently sensitive.…”
Section: Introductionmentioning
confidence: 99%